Occupational risk of lung cancer among lifetime non-smoking women in Shanghai, China. Issue 10 (21st July 2009) - Pronk, A; Coble, J; Ji, B-T; Shu, X-O; Rothman, N; Yang, G; Gao, Y-T; Zheng, W; Chow, W-H
Abstract : Objectives: Occupational lung carcinogens have been primarily studied in men. The aim of this study was to investigate occupational lung cancer risk in a cohort of Chinese non-smoking women. Methods: In 1996–2000, 71 067 non-smoking women who had held a job outside the home were interviewed for the prospective Shanghai Women's Health Study in China. Exposure to lung carcinogens was assessed by matching occupation and industry titles from lifetime occupational histories with lists of jobs identified by the International Agency for Research on Cancer to have potential exposure to: (1) known (A-list); or (2) suspected (B-list) carcinogens. In addition, similar occupational titles were grouped independent of the a priori defined lists. Relative risks (RRs) were calculated using Cox proportional hazards regression. Results: During follow-up through 2005, 219 incident lung cancer cases were diagnosed. Jobs on the A-list and B-list were held by 0.8–6.7% and 2.7–9.4% of the cohort, respectively. Overall, ever holding any job on the A-list or B-list was not associated with lung cancer incidence. Indications of excess risk were found for two subgroups: painters (A-list) and rubber workers (B-list) (RR  =  2.0 and 1.7, respectively, p⩽0.1). An exploratory analysis of 35 occupational categories independent of the lists showed significantly increased risks for leather products/shoes, wood/paper products and miscellaneous production/transportation. The former two of these categories were similar to subgroups of the B-list, but broader than the specific a priori defined jobs. Conclusions: Significantly elevated lung cancer risk was associated with employment in some broad occupational categories that also included jobs with potential exposure to suspected carcinogens (B-list). The results suggest that although similar exposures to those described on the B-list may play a role in this cohort of Chinese women, carcinogenic exposure may not be restricted only to the jobs on the B-list.